Obtaining of Carbon Nanotubes in Reactor with Fluidized Bed of Catalyst - Smagulova, Gaukhar; Kaidar, Bayan; Vassilyeva, Natalia; Prikhodko, Nikolay (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
The researching activity related to CNTs has grown most significantly over the past 10 years. Since 2006, world capacities of production of CNTs have increased 10-fold. The annual number of scientific publications on CNT and issued patents continues to grow [1]. Carbon nanotubes are used in many areas, such as energy, biotechnology, microelectronics, textiles, etc....
Keywords: carbon nanotubes